Effect of the accelerated aging condition on some physiological and biochemical changes in seeds of rice (Oryza sativa L.) - Marwa A.Abbas; Muhannad M. Sahib (Al-Qadisiyah Journal of Pure Science, 2018)
This study was conducted in the plant laboratory in the Faculty of Science / University of Qadisiya in the academic year 2015 and 2014_ included a study of the physiological and biochemical changes that occur during the accelerated ageing conditions (0.3, 6, 9.12) day to plant the seeds of rice. Seeds subjected to the accelerated ageing conditions (45 Â± 1 Â° m and 100% relative humidity) for 3, 6, 9 and 12 days and were compared with the seeds of the control (non aged) to evaluate physiological and biochemical changes . Accelerated ageing seed caused for some of the physiological and biochemical characteristics. Has increased the relative moisture content of the seeds exposed to the accelerated ageing and is proportional with the increase in the ageing  period of (7.47)% when the control treatment to (40.80)% when the treatment 12 days. Protein content decreased from (3.29) mg / ml in the control treatment to (1.84) mg / mL at treatment of 12 days. Low starch content of (538.79) mg / g in the control treatment to (182.65) mg / g at the treatment of 12 days. The MDA content also increased in direct proportion with the increase in the ageing period, which amounted to the highest value (129.33) mol / g at the treatment of 12 days. There was also a decrease in the effectiveness of the enzyme catalase and an increase in the effectiveness of enzymes the protease and Î±-amylase and polyphenol oxidase  with an increased ageing period.